ANALISIS FAKTOR-FAKTOR PENDUKUNG PENGUATAN CALON PENYULUH PERTANIAN AHLI UNTUK PEMBANGUNAN KETAHANAN PANGAN - Yoyon Haryanto (Jurnal Penyuluhan Pertanian, 2020)
The improvement of understanding for agricultural extension worker candidates on the duties and function of agricultural extension and food security in the STPP Bogor had never been properly measured. Characteristics of area of origin, formal education, non formal education, field of expertise and mastery level of perception the material were all factors supporting the strengthening of agricultural extension worker in STPP Bogor. The aim of this research was to analyze the candidates understanding of agricultural extension worker on basic tasks and functions, food security, and to formulate strategies that support the curriculum development of these competencies. The method used in this study was complete enumeration which processed by descriptive, correlation, and multiple regression analysis. The result of this study showed that factor influencing the basic tasks and functions, and food security was the characteristic of local origin. This result was also strengthened with the relationship between the origin of agricultural extension worker candidate against level of understanding of the basic tasks and functions, and knowledge of food security. Agricultural extension worker candidate from West Indonesian Region had better understanding than Central and East Indonesian Regions. Shared commitment among all parties involved in the process of education and increased capacity of agricultural extension worker candidates in providing agricultural extension agents who had a double competence was essential to improve understanding on duties and function.